Many years of experience of spontaneous pneumothorax treatment within one medical center - A. V. Mikheev; S. N. Trushin (Туберкулез и болезни лёгких)
The objective: to analyze results of surgical treatment of the patients with spontaneous pneumothorax.Subjects and Methods. Medical records of patients with spontaneous pneumothorax (SP) who were treated in Surgical Thoracic Department of Ryazan Regional Clinical Hospital from 1998 to 2021 were retrospectively analyzed. The article describes the experience of treatment of 738 cases of spontaneous pneumothorax within one medical center. The evolution of tactics and principles of surgical treatment over a 23-year period is presented. The incidence of spontaneous pneumothorax and efficacy of different surgical options were analyzed. The recurrence of spontaneous pneumothorax was recorded in the following cases: after pleural cavity drainage – in 19.7%, after videothoracoscopic resection of bullous parts of the lung in combination with subtotal parietal pleurectomy – in 2.1%.